Fixed points of two interpolative cyclic contractions in b-metric spaces - Darsana Devi; Pradip Debnath (Heliyon)
The b-metric space happens to be one of the of most significant and non-trivial generalizations of metric spaces. In this paper, we introduce the concepts of Kannan type and Ćirić-Reich-Rus type cyclic contractions in b-metric spaces via interpolation. Existence and uniqueness of fixed points of these two newly introduced contraction mappings have been studied and validated with suitable examples. Our paper also generalizes, extends and provides improvements to the results in the recent paper by Edraoui et al. (2023) [11].